Prevalence and pattern of alcohol consumption using alcohol use disorder identification test among students at a medicalcollege in Goa, India - Verenkar, Yash Jairam; Vaz, Frederick Satiro (International Journal Of Community Medicine And Public Health, 2018)
Background: Alcohol use is a complex health and social issue, especially in developing countries like India and in particular the western Indian state of Goa moreover, adolescents are usually more vulnerable to alcohol-related harm from a same volume of alcohol compared to other age group individuals. Methods: A cross-sectional design was conducted over a period of two months in Goa medical college, Goa. Students pursuing the MBBS Course in all semesters for the academic year 2015-16 were the study partici pants. Data was collected by interviewing the students. The pre-tested structured questionnaire used to collect the data. Alcohol consumption pattern was assessed using alcohol use disorder identification test (AUDIT). Approval was obtained from the Institutional Ethics Committee of the Medical College. Informed written consent was obtained from the participant prior to the interview. SPSS Software Package was used for statistical analysis. Results: Prevalence of alcohol consumption was found to be 39.4%. Prevalence among females was higher (40.6%) compared to Males (38%). Among the alcohol consumers 82.3% were light drinkers (AUDIT <8) while 17.7% were identified as heavy drinkers. Hazardous alcohol consumption was identified in 46.7% of alcohol consumers. 20.9% of alcohol consumers showed signs of alcohol dependence. Conclusions: Awareness of ill effects of alcohol consumption, counselling to deal with stress related to studies, negotiating peer pressure etc. need to be the possible solutions to address this health and social issue of alcohol use among young adults.